Visual Standards for Civil Aviation - Backman, H A (Canadian Journal of Optometry, 1984)
Standards for personnel licensing are established by the International Civil Aviation Organization. These standards and procedures are set without investigation concerning their validity and are revised occasionally. The procedures for the ophthalmic examination are often beyond the competence of the aviation medical examiner. Recommendations are made to develop new improved standards and procedures. A complete professional oculo-visual examination should be required on a regular basis for re-licensing civil pilots.